Synthesis of (2E)-2-methyl-3-(4-([4-(quinolin-2-ylmethoxy)phenyl]sulfanyl)phenyl)prop-2-enoic acid (VUFB 20609) and 2-methyl-3-(4-([4-(quinolin-2-ylmethoxy)phenyl]sulfanyl)phenyl)propanoic acid (VUFB 20584) as potential antileukotrienic agents - Jampílek, J; Dolezal, M; Kunes, J; Víchová, P; Jun, D; Hanika, Jirí; O'Connor, R; Clynes, M (The Journal of pharmacy and pharmacology, 2004)
The syntheses of (2E)-2-methyl-3-(4-([4-(quinolin-2-ylmethoxy)phenyl]sulfanyl)phenyl) prop-2-enoic acid (VUFB 20609) and racemic 2-methyl-3-(4-([4-(quinolin-2-ylmethoxy) phenyl]sulfanyl)phenyl)propanoic acid (VUFB 20584) as new potential antileukotrienic drugs are described. Due to a low reactivity of the 4-substituted aryl bromides (coupling of the 4-substituted aryl bromides do not provide an activating functional group with 4-methoxybenzene-1-thiol), special conditions, in particular specific heterogeneous copper catalysts, were used. Catalytic hydrogenation of the conjugated double bond on Pd/C in the presence of the sulfanyl group is discussed. In-vitro cytotoxicity testing was performed using a microplate colorimetric acid phosphatase assay. Antiplatelet activity was evaluated using an in-vitro test in human platelet-rich plasma. Some substances inhibited arachidonic acid-induced platelet aggregation.
Keywords: buněčná smrt; nádorové buněčné linie; Quinolines; sulfidy; Leukotriene Antagonists; Stereoisomerism; Arachidonic Acid; lidé; hydrogenace; Cell Line, Tumor; Sulfides; inhibitory agregace trombocytů; Cell Death; stereoizomerie; Platelet Aggregation Inhibitors; Humans; molekulární struktura; kyselina arachidonová; Hydrogenation; chinoliny; antagonisté leukotrienů; Molecular Structure